An investigation of influence op radial throw of the cutting elements on the tool life of face milling cutters - Vasić, Siniša; Milikić, Dragoje; Kovač, Pavel (Journal of Production Engineering, 2023)
The cutting edges of face milling cutters have axial throw (in direction of the tool axis) and radial throw (in a perpendicular direction to the axis of the tool)."In the work, the results of research of influence of the radial throw on the tool life of face milling culters are shown. The cutting _Ionditions are kept constant througout the experiment and developing of wear on the back flank of the tooth is examined. The experiment has proved that the chip load, as well as the tool life are influenced by the radial throw.